Karakteristik Nata De Soya Limbah Cair Tahu Dengan Penambahan Gula Batu - Ika Azahra, Rismantia; Wati, Desti Ambar; Lestari, Lara Ayu; Junita, Dera Elva (Jurnal Gizi Aisyah, 2024)
Nata de soya is a functional food source of fiber made from liquid tofu waste which is formed from the fermentation process. Nata is made through a non-spontaneous fermentation process by adding the starter Acetobacter xylinum and will grow optimally at a temperature of 28-31oC, pH 3.5-7.5. Success in making nata is determined by adding ingredients, one of which is a source of carbohydrates. This research aims to determine the characteristics physical and chemical of nata de soya with the addition of a carbohydrate source in the form of rock sugar. Based on proximate tests and thickness measurements on nata de soya with rock sugar, the results obtained were 96.7% water content, 0.2% ash, 0.2% fat, 5.0% crude fiber, 7.7% carbohydrates and thickness measurement results Nata 1 cm.